Kajian Perubahan Garis Pantai Kabupaten Bengkulu Utara dengan Interpretasi Citra Penginderaan Jauh dan Digital Shoreline System - Septianingsih, Dwi; Amalia, Isra; Johan, Septi; Lidiawati, Liza (Jurnal Fisika Unand, 2025)
The coastal area of ​​North Bengkulu often experiences abrasion and accretion processes, considering its location directly facing the vast waters of the Indian Ocean. This phenomenon can have an impact on changes in the coastline in the area. This study aims to identify changes in the coastline over time by utilizing multi-sensor satellite imagery from USGS. The focus is to measure changes in the distance of coastal areas in North Bengkulu Regency. Changes in the coastline in this area are calculated statistically using the Digital Shoreline Analysis System (DSAS). The results of the average calculation of the distance of changes in the coastline from 2014 to 2023 in North Bengkulu Regency are influenced by quite large abrasion and accretion of -20.31 meters and 21.6 meters. The impact of accretion shows a higher value than abrasion due to the addition of land (sedimentation) in a number of river estuaries in North Bengkulu Regency. Changes in the coastline are influenced by the dynamics of seasonal winds and sea waves due to the East and West Monsoons, impacting coastal settlements, infrastructure, and ecosystems such as coral reefs and mangrove forests